GEOLOGI DAERAH BATU CERMIN, SAMARINDA UTARA, KOTA SAMARINDA, KALIMANTAN TIMUR - Mangalik, Dian (Journal Geological Processes, Risks, and Integrated Spatial Modeling, 2025)
Batu Cermin is located in Kelurahan Sempaja Utara, Samarinda Utara District, Samarinda City, East Kalimantan Province, within the Lower Kutai Basin. This area exhibits a complex stratigraphic and structural geology, featuring outcrops from the Pulau Balang Formation and Bebuluh Formation. Field observations identified lithological similarities between these formations, highlighting the distinctive characteristics of different depositional environments. Geological mapping in Batu Cermin was conducted to obtain detailed data on lithology, morphology, slope gradients, drainage patterns, and structural geology. This process involved a combination of field observations and satellite imagery analysis. The mapping results provide a comprehensive understanding of the dominant lithology, geological history, and the relationships between formations within the study area. A total of 34 observation stations were distributed over a 1 km² area, focusing on lithological, morphological, and structural geological observations. Based on the mapping results, the Batu Cermin area consists of three primary rock units: Batu Cermin Mudstone Unit, Batu Cermin Limestone Unit, and Batu Cermin Sandstone Unit. These three units exhibit a conformable stratigraphic relationship. Geomorphologically, Batu Cermin shows a monocline ridge (S11), forming steep hills with a dendritic drainage pattern, as well as denudational features such as eroded hills (D1) and nearly flat plains (D5) with gentle to moderate slopes. The main geological structure in this area includes shear joints, which formed as a result of dominant stresses oriented in a Southeast-Northwest direction, with additional stress from the Northeast-Southwest, indicating tectonic activity that has influenced the region.